Preliminary results from the Partner Availability Limitations Study (PALS): Clinical trial design and implementation. (7th December 2020) - Largent, Emily A.; Clapp, Justin; Sykes, Olivia; Abera, Maramawit; Harkins, Kristin; Grill, Josh D.
Abstract: Background: Alzheimer's disease (AD) clinical trials, even trials recruiting cognitively normal populations, require participants to enroll with a "study partner" (SP). SPs serve as knowledgeable informants, reporting on participants' cognitive and functional performance. The SP requirement can be a barrier to research participation, especially if an older adult doesn't have someone able or willing to enroll with them. Method: Participants in this qualitative study are adults aged 60‐85 who previously signed up to participate in either the University of California, Irvine Consent to Contact Registry (C2C) or the University of Pennsylvania Brain Health Research Registry. Respondents participate in semi‐structured interviews covering: (1) social supports; (2) willingness to ask someone to be their SP; (3) whom they would ask; and (4) ways of increasing SP participation. Individuals identified as likely to be asked to be a SP are subsequently recruited to participate in semi‐structured interviews covering similar domains. Sixty potential AD trial participants and 30 potential SPs are being interviewed. All interviews are recorded, transcribed, and coded. Coding is managed with NVivo 12.0. The University of Pennsylvania IRB approved this study. Results: Most respondents identify at least one person—typically a family member or close friend—who could be their SP. When identifying a potential SP, respondents consider their relationship with and personal traits of the SP, as well as the logistics of research participation. Willingness to ask that individual to fill the SP role varies. The SP role is seen as burdensome, with the relative level of burden dependent on non‐research demands on the SP's time and attention (e.g., family and work). Respondents believe that the SP role has numerous benefits for the participant (e.g., emotional/logistical support), the SP (e.g., positive feelings), and the researchers (e.g., additional source of data). Offers of payment to the SP and flexible study visits (e.g., nights/weekends or virtual appointments) would increase willingness to ask a SP. Conclusion: Our results indicate that identifying someone able and willing to serve as a SP can be challenging for older adults interested in AD clinical trials, but modifications of study design may help overcome this barrier.